Faktor yang Memengaruhi Rendahnya Minat Penggunaan Metode Kontrasepsi Jangka Panjang Intrauterine Device di Kampung Keluarga Berencana - Emi Sutrisminah; Fifiana Lisani; Isna Hudaya (Faletehan Health Journal, 2023)
Indonesians have relatively little interest in intrauterine device (IUD) as a long-acting birth control option. The low interest in IUD is due to the difficulty of determining contraceptive options as perceived by family planning acceptor. Factors influencing the interest of using IUD include knowledge, perception of the side effects, and husband support. This research aimed to determine the relationship between knowledge, perception of side effects and husband support to the low interest in the use of IUD. This research used analytical descriptive method and a cross-sectional approach. The population of this study was 393 family planning acceptors and the samples were 76 of them. The research instrument was a questionnaire. The data analysis used chi-square test. The results of the study showed a significant relationship between perception of side effects and low interest in IUD with p value 0.000. There was a significant relationship between husband's support and low interest in the use of IUD with p value 0.005. There was no significant relationship between knowledge and low interest in the use of IUD with p value 0.143. The researcher concluded that sufficient and good knowledge of IUD does not guarantee family planning acceptors to have an interest to use IUD. Their perception greatly influences the decision making of used-contraception type. Furthermore, husbands support significantly influence wife decision of using long-acting birth control options.